Associations of lower limb joint asymmetry with fatigue and disability in people with multiple sclerosis. (May 2020) - Workman, Craig D.; Fietsam, Alexandra C.; Rudroff, Thorsten
Abstract: Background: An early symptom of multiple sclerosis is unilateral weakness, particularly in the lower limbs, which is associated with strength asymmetries. The purpose of this exploratory study was to examine strength asymmetries at the hip, knee, and ankle joints, and to investigate the associations between lower limb strength asymmetries and self-reported fatigue severity and disability in people with multiple sclerosis. Methods: Sixteen mildly-disabled people with multiple sclerosis (females = 9) completed isokinetic maximal voluntary contractions of the hip extensors and flexors, knee extensors and flexors, and ankle plantar flexors and dorsiflexors. Asymmetry indices between the strength of the more- and less-affected lower limbs at each muscle group and the percent agreement between self-reported and objectively-determined more-affected lower limb were calculated. Patient Determined Diseases Steps and Fatigue Severity Scale were also completed. Findings: All joints showed asymmetry (asymmetry indices ≥10%). Knee flexors (mean [SD]; 49.9 [37.8%]) and ankle plantar flexors (46.6 [35.5%]) had the largest asymmetry indices. Hip and knee extensors had the lowest asymmetry indices (21.1 [18.1%] and 30.1 [24.7%], respectively) and the highest agreement between self-reported and objectively-determined more-affected lower limb (93.3 and 93.8, respectively). The hip extensor asymmetry index was correlated with the Fatigue Severity Scale ( r = 0.542, p = 0.037). Interpretation: For the assessment of strength asymmetries in people with multiple sclerosis, it is suggested to 1) include measures of hip, knee, and ankle strength asymmetries, 2) include subjective perceptions and objective measures of strength asymmetries concurrently, and 3) to include measures of sensory function (proprioception). Highlights: Strength asymmetries between the more- and less-affected legs were examined. Self-reported and objectively-determined more-affected leg agreement was calculated. The hip extensors were associated with subjective reports of fatigue. More-affected leg agreement was highest at the hip and knee extensors.